Electron doped superconducting cuprates for photon detectors. (July 2018) - Romano, P.; Riccio, M.; Guarino, A.; Martucciello, N.; Grimaldi, G.; Leo, A.; Nigro, A.
Abstract: The study of unconventional materials with peculiar properties is a fundamental step for the design and advancement of superconducting photon detectors. Nd2−x Cex CuO4±δ is a non-traditional cuprate superconductor exhibiting n-type conduction which properties can be changed by modifying its cerium and oxygen content. Ultra-thin films of this compound have been deposited by dc sputtering technique, and systematically characterized by using X-ray diffraction and electrical measurements. Design and patterning of sample geometries have been performed by optical and electron beam lithography in order to obtain sub-micron wide strips for measurements of photon detection.